Assessing the usability of aromatic mouthwashes in alleviating physiological stress responses - Dilrukshi, E. A. Chayani; Ogino, Tatsuki; Ishikawa, Mami; Kuroda, Hiroki; Nomura, Shusaku (Frontiers in Oral Health, 2024)
Background: Mouthwashes play a pivotal role in oral care, and their efficacy has been explored extensively across various dimensions. As a contribution to the development of novel oral care products, this study aims to investigate the psychophysiological effects of aromatic mouthwashes during the resiliencecovery period from a short-term cognitive stressor utilizing biological signals and subjective evaluations.A within-participant experimental design with 22 healthy females was conducted with four mouthwashes; peppermint (Mint), peppermint + bergamot (MB), peppermint + sweet orange (MO), and peppermint + lavender (ML), and water as the control (Ctl), after a 20-minute calculation task. Subjective evaluations and physiological responses including skin conductance level and electrocardiogram were recorded throughout the experiment.Results: Citrus mouthwashes (MO and MB) showed a greater decrease in heart rate and a significant increase in the high-frequency component of heart rate variability. The participants indicated a significant effect in terms of "flavor preference" and "refreshing sensation" for mouthwash use compared to the Ctl.The results suggest that rinsing with citrus-flavored mouthwashes has a positive impact in alleviating the physiological stress response (in terms of cardiac activity). These findings may have implications for the development of innovative, novel oral care products that promote stress reduction and improve oral health.